Swift and Certain Probation as a HOPE-Like Model: Progress toward Goals and Lingering Challenges. Issue 1 (1st January 2023) - Frailing, Kelly; Rapp, Victoria; Taylor, Rae
ABSTRACT: The Swift and Certain Probation Program in Jefferson Parish, Louisiana is a HOPE-like program that provides intensive supervision to high-risk probationers. The current study describes the first 2 years of the Swift and Certain (SAC) Probation program in Jefferson Parish, LA. We examine progress toward five of the seven program goals, including reduction of substance use, reduction in prison overcrowding, increase in effective resource use, reduction in new crimes, and increase in personal and societal responsibility. We find that the program appears to meeting these five goals and we contextualize these findings with a description of participants' experience in the program that includes results of a perceptions survey. However, progress on the other two goals has remained more elusive and we discuss the challenges for the program in meeting these, and conclude with implications for both research and practice.